Iconic Studies Relevant for Research in Marketing and the Journal of Global Scholars of Marketing Science - Woodside, Arch (Taylor and Francis, 2015)
Here, an “icon” refers to a study widely and critically admired, a study symbolizing a movement or field of activity; iconic marketing studies offer exceptional contributions to marketing theory and/or data collection, and/or data analysis, and/or interpretations/ implications of qualitative and/or quantitative empirical findings. This article identifies antecedent conditions associated with achieving iconic status in research in marketing and proposes 10 tenets useful for identifying and planning iconic studies in marketing. The study reviews examples of iconic studies in the marketing literature. The study also addresses a few telling mistakes that researchers in the marketing discipline frequently make. The study of iconic research is helpful for crafting high-quality theory and planning high-quality research designs, as well as increasing vigilance and skill in identifying truly exceptionally high-quality studies and studies that are plainly just bad. The essay briefly reviews 10 JGSMS articles appearing also in this virtual issue as possible candidates for the achievement of iconic status in marketing.